Bismuth and Chlorine Dual-Doped Perovskite Chloride as a Phase-Structure-Stable and Moisture-Resistant Solid Electrolyte for Chloride Ion Batteries - Xia, Tianchen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.